Relational fragility, development and an emerging self: service user views of engaging in an IIRMS in the OPD pathway. Issue 3 (7th August 2019) - Ryan, Sue; Gordon, Frances; Gordon, Neil
Abstract : Purpose: The purpose of this paper is to gain an in-depth view into how participants perceived their experience of engaging in an enhanced Intensive Intervention and Risk Management Service (IIRMS), which is a part of the Offender Personality Disorder (OPD) pathway based within the community. Design/methodology/approach: Five participants were interviewed. They were at different points of engagement with the service. Interviews were taped, transcribed and analysed using the grounded theory methodology. Findings: Participants were able to provide in-depth reflections about their experiences at the service. The main issues centred upon "managing fragile relationships" and "an emerging self". Subcategories linked to managing fragile relationships were: "letting people in and keeping them away"; "surviving the ruptures"; and "treating me like a person". Subcategories linked to an emerging self were: "readiness to change" and "making new connections". Research limitations/implications: This study focused upon one enhanced IIRMS and findings are not necessarily generalisable to other services within the OPD pathway, although themes are likely to resonate for those leaving custody with complex interpersonal difficulties. Practical implications: This study has provided access to participants' perspectives on engaging with an IIRMS. Many factors impact upon the individual's journey, which is central to the relational approach underpinning the pathway. Originality/value: The findings have important messages for service providers and commissioners and crucially service user perspectives have been obtained that are integral to future development of the OPD pathway. The findings are also relevant for released prisoners attempting to reintegrate within the community.